SPEI-based spatial and temporal evaluation of drought in Somalia - Nyaga, Justine M.; Musei, Sylus Kipngeno; Dubow, Abdi Zeila (Elsevier, 2020)
Somalia is one of the most drought prone countries both in Africa and globally. Drought events usually develop gradually unnoticed, causing tremendous effects on both agriculture and environment. This study evaluated the spatio-temporal variations of drought occurrences in Somalia for the period between 1980 and 2015 as quantified by Standardized Precipitation Evapotranspiration Index (SPEI). The intensities, frequencies and trends of drought occurrences were analyzed using SPEI for the multiple timescales of 1-, 3-, 6-, 12-, and 24-month. The temporal variations in drought showed decreasing trends in severity and increasing trends in drought duration as the SPEI timescales increases. The major drought event as identified by SPEI 12 occurred during the period between May 2011 and January 2013 lasting for a period of 12 months with an intensity of 􀀀 0.55. Furthermore, drought count was generally high in the southern parts of Somalia and entire country had suffered droughts ranging from moderately dry to severely dry conditions. An average drought duration of between 2 and 3 months was recorded for most (81%) of the locations. The results of this study could be used to support the water resources management, and to promote the realization of environmental protection and crop production in future.
Keywords: Somalia; Spatio-temporal; Drought; SPEI